2015
DOI: 10.3923/rjvs.2015.21.28
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Leptospira Antibodies in Cattle Slaughtered for Sale in Some North Central States of Nigeria

Abstract: Leptospirosis, a disease of livestock, has great economic impact on the agricultural industry because it causes abortions, stillbirths, infertility, reduced milk production and death in livestock. Moreover, when successfully transmitted to man, it may result in multisystem febrile illness, with hepatic, renal and pulmonary involvement and high mortality rates. This research determined the sero-epidemiology of Leptospira antibodies using, Microscopic Agglutination Test (MAT) in slaughtered cattle in selected st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Cattle act as classic reservoirs of serovar Hardjo (Rajala et al, 2017;Loureiro and Lilenbaum, 2020). A similar observation was reported by Abiayi et al (2015) in slaughtered cattle in Nigeria where the predominant serovars were Hardjo (27.8 per cent) and Grippotyphosa (25.6 per cent) with the seroprevalence of 57.9 per cent. Natarajaseenivasan et al (2011) also found that, serovar Hardjo was one of the predominant serovars in cattle from samples collected from southern India.…”
Section: Resultssupporting
confidence: 78%
“…Cattle act as classic reservoirs of serovar Hardjo (Rajala et al, 2017;Loureiro and Lilenbaum, 2020). A similar observation was reported by Abiayi et al (2015) in slaughtered cattle in Nigeria where the predominant serovars were Hardjo (27.8 per cent) and Grippotyphosa (25.6 per cent) with the seroprevalence of 57.9 per cent. Natarajaseenivasan et al (2011) also found that, serovar Hardjo was one of the predominant serovars in cattle from samples collected from southern India.…”
Section: Resultssupporting
confidence: 78%
“…In Nigeria, antibodies to several pathogenic leptospires have been detected in livestock slaughtered for human consumption and in pets and rodents suggesting high risk of exposure and infection to humans (Abiayi et al, 2015;Ajayi et al, 2017Ajayi et al, , 2020Ngbede et al, 2012;Okewole & Ayoola, 2009;Udechukwu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, there are several studies using serological or culture methods that reported the detection of Leptospira spp. with varying prevalence in humans (Ezeh et al, 1990;Ngbede et al, 2012), rodents (Ajayi et al, 2017;Diallo & Dennis, 1982;Udechukwu et al, 2021) and other animal species (Abiayi et al, 2015;Ajayi et al, 2020), supposing their involvement in the epidemiology of the disease in Nigeria. However, there are no documented molecular studies on leptospirosis in animals and men in Nigeria.…”
mentioning
confidence: 99%
“…(i.e. 23,558,674) of Nigeria"s population which is put at 173,905,439 and has been a major contributor to national net food production, Abiayi, et al [8].…”
Section: Study Areamentioning
confidence: 99%